THE RELATION OF OVERPROTECTIVE PARENTING WITH EARLY CHILDHOOD SPEECH ABILITY IN THE DIGITAL ERA - An An Andari; Diden Rosenda; Asep Supriadi AA (UPI Kampus Cibiru, 2018)
Abstract:. The progress of the time is very influential to the world civilization. In the era of globalization, all forms of social interaction are replaced with all-digital equipment. It is characterized by the popularity of sophisticated electronic equipment ranging from television, cell phone, internet and other communication tools. The progress of the time affects the nurture that given by parents to children. Overprotective parenting is an excessive nurture of parent to their children. By reason of fear, the parents do not give a freedom to the children to do their preferred activity, beside that, there are still many parents who provide communication tools that are not appropriate with the age, needs and development of their children. This research aims to determine whether there is a relationship between an overprotective parenting to the speech ability of early childhood children. The study was conducted in Laboratory Kindergarten of UPI Cibiru Bandung regency, with 24 respondents. The instruments which are developed in this study are the instrument of overprotective parenting and instrument on children's speech ability. The data collection was done by questionnaire. The research uses correlational descriptive methods, and the data analysis used a correlation test. The results showed a correlation of (0, 03830.05), then Ho is rejected, it means that there is a significant relationship between overprotective parenting style with the children’s speech ability in early childhood in the Laboratory Kindergarten of UPI Cibiru, Bandung regency.Keyword: Parenting, overprotective, speech ability Abstrak: Kemajuan jaman sangat berpengaruh terhadap peradaban dunia, di era globalisasi ini segala bentuk interaksi sosial banyak yang tergantikan dengan alat-alat serba digital, hal ini ditandai dengan maraknya alat elektronik yang canggih dari mulai televisi, hanphone, internet dan alat komunikasi lainnya. Kemajuan jaman juga berpengaruh terhadap pola asuh yang diberikan orang tua terhadap anak, masih banyak orang tua yang memberikan alat komunikasi yang tidak sesuai dengan kebutuhan dan usia perkembangan anak. Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara pola asuh over protektif terhadap kemampuan bicara anak usia dini. Penelitian dilakukan di Taman kanak-kanak Laboratorium UPI Cibiru Kabupaten Bandung dengan responden sejumlah 24 orangtua. Instrumen yang dikembangkan dalam penelitian ini yaitu instrumen tentang pola asuh dan instrumen tentang kemampuan berbicara anak usia dini. Pengumpulan data dilakukan dengan kuisioner. Penelitian ini menggunakan metoda deskriptif korelasional, analisis data menggunakan uji korelasi. Hasil penelitian menunjukkan terdapat hubungan yang positif, kuat dan signifikan dengan korelasi sebesar (0,0383 0,05) maka Ho ditolak, artinya bahwa ada hubungan signifikan antara pola asuh over protektif dengan kemampuan berbicara anak usia dini di Taman Kanak-kanak Laboratorium UPI Cibiru Kabupaten Bandung.Kata Kunci: Pola Asuh, Over Protektif, kemampuan Berbicara